O-306 LINZAGOLIX FOR ENDOMETRIOSIS-ASSOCIATED PAIN: SAFETY RESULTS FROM EDELWEISS 3, A PHASE 3, RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED TRIAL. (30th June 2022) - Donnez, J; Taylor, H; Gemzell-Danielsson, K; Catherino, W; Bestel, E; Gotteland, J.P; Humberstone, A; Moore, L; Garner, E
Abstract: Study question: Is once-daily linzagolix treatment for women with moderate to severe endometriosis-associated pain (EAP) safe for use for up to 6 months of treatment? Summary answer: Both doses of linzagolix were well-tolerated with minimal BMD decrease and few TEAEs >5% in either linzagolix arm. What is known already: Linzagolix (LGX) is an investigational once-daily oral GnRH receptor antagonist that reduces serum estradiol in a dose-dependent manner and is being developed in two dosages for the treatment of endometriosis-associated pain (EAP): 75 mg, and 200 mg dose with hormonal add-back therapy (ABT).  Study design, size, duration: EDELWEISS 3 is a randomized, double-blind, placebo-controlled, multicenter Phase 3 trial of linzagolix in women with moderate to severe EAP. The trial includes 3 treatment arms: 75 mg LGX, 200 mg LGX with ABT (E2 1 mg/ NETA 0.5 mg), or placebo. Here we present safety results up to 6 months (24 weeks) of treatment. Participants/materials, setting, methods: Eligible reproductive-aged women with moderate-to-severe EAP were randomized and treated (n = 484) for 6 months with 75 mg LGX, 200 mg LGX with ABT (E2 1 mg/ NETA 0.5 mg), or placebo. Safety and tolerability objectives reported here include 6-month results for treatment emergent adverse events (TEAEs), assessment of mean percent change from baseline (CfB) in lumbar spine (LS) bone mineral density (BMD) and Z-scores. The safety analysis set included 484 subjects across the 3 treatment groups. Main results and the role of chance: The overall incidence of TEAEs was similar between the placebo and LGX 75 mg group (46.9%) and slightly higher (56.8%) in the LGX 200 mg + ABT group. There were few (3) serious TEAEs, and none were related to LGX. TEAEs that occurred in over 5% of patients in either active treatment arm included headache (10.5%, 8.1%, and 8.0%), hot flush (6.8%, 7.5%, and 2.5%), and fatigue (6.8%, 3.8%, and 2.5%) for the 200 mg LGX with ABT, 75 mg LGX, and placebo groups, respectively. Mean percent CfB (95% CI) in LS BMD was -0.79% (-1.15,  -0.43%), -0.89% (-1.31, -0.47%), and +0.78% (0.41, 1.15%) for the 200 mg LGX with ABT, 75 mg LGX, and placebo groups, respectively. Z-scores at 6 months remained within the same range as baseline in all groups. Limitations, reasons for caution: Additional efficacy and safety results from the trial's 24 weeks (6 mo) extension phase are pending. (Edelweiss 6 protocol: NCT04335591) Wider implications of the findings: These results support further development of ABT and non-ABT doses of linzagolix that have potential to provide flexibility and choice for women seeking treatment for EAP. A non-ABT option is important for women who have a contraindication to, are at increased risk for complications, or prefer not to use ABT. Trial registration number: ClinicalTrials.gov: NCT02778399